EFEK MOTIVASI TERHADAP KINERJA SECURITY PT. PEGATRON TECHNOLOGY INDONESIA BATAM - Lutfi Erwin Lubis; Diamon Sembiring; Wirasman Mendrofa (Ensiklopedia of Journal, 2023)
This study aims to determine and analyze the effect of employee motivation (X) on the Security Performance of PT. Pegatron Technology Indonesia Batam. The research method applied is a quantitative research method. Data collection was carried out by distributing questionnaires to 56 respondents from a population of 65 people. Determination of the sample using the Slovin formula. In this study, data analysis techniques used validity test, reliability test, classic assumption test (normality test) simple linear regression analysis with the help of SPSS version 20 software. Based on the results of linear regression statistical calculations, it was proven that the variable Motivation (X) had no positive effect and significantly to employee performance (Y) with a Sig.count value of 0.641> α = 0.05.